2001
DOI: 10.1046/j.1464-410x.2001.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evaluation of transcatheter arterial embolization for unresectable renal cell carcinoma with distant metastasis

Abstract: Objective To evaluate the ef®cacy of transcatheter arterial embolization (TAE) in patients with unresectable renal cell carcinoma (RCC) and distant metastasis at the time of diagnosis. Patients and methods The study included 54 patients with histologically de®ned RCC (by biopsy in 28 and autopsy in 26) who were unable to undergo nephrectomy mainly because their performance status was poor (score o 2). The patients were classi®ed into two groups; 24 patients who underwent TAE with ethanol and 30 patients who di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 18 publications
3
32
0
3
Order By: Relevance
“…Polyvinyl alcohol, absolute ethanol and gelatin sponge were also used. Onishi et al applied only ethanol in a group of patients with RCC [14]. Munro et al most often used ethanol combined with other agents (alcohol with coils in 85%, alcohol and gelatin sponge in 8%, in 7% only alcohol) [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Polyvinyl alcohol, absolute ethanol and gelatin sponge were also used. Onishi et al applied only ethanol in a group of patients with RCC [14]. Munro et al most often used ethanol combined with other agents (alcohol with coils in 85%, alcohol and gelatin sponge in 8%, in 7% only alcohol) [10].…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms were controlled using analgesics and antiemetic drugs. Other authors observed the symptoms of PES in over 80% of patients [8,14]. May et al analyzed 227 embolization procedures and observed PES in 89% of cases with a predominance of pain (100%) and fever (49%) [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…www.impactjournals.com/oncotarget When combined with IT, there is no survival benefit of RE, with or without subsequent CN [17], and survival could even be lower, as reported by Demirci et al : median survival for RE of 1 (range, 1-74) months compared to 11 (range, 1-80) months for CN [18]. Although RE improved survival from 229 days to 7 months, compared to NT, survival was still lower than the 17.8 months for palliative nephrectomy [19,20]. In our dataset (Supplementary Table 1), the longest survival among patients with an intermediate risk classification was achieved with CN, followed by NT and RE, regardless of IT or TT treatment.…”
Section: Discussionmentioning
confidence: 84%